2016
DOI: 10.3906/vet-1506-59
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ovulatory follicle size at the time of insemination onpregnancy rate in lactating dairy cows

Abstract: The aims of this study were to determine the factors that affect follicle size at the time of artificial insemination (AI) and to detect the relationship between ovulatory follicle size at the time of AI and pregnancy rate in dairy cows. A total of 1428 follicle size measurements were obtained from Holstein-Friesian (HF) and Swedish Red (SR) cows that were inseminated with the fixed-timed AI protocols used in this study. Follicle size was affected by breed (P = 0.0001), milk production (P = 0.01), parity (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
(121 reference statements)
1
15
0
7
Order By: Relevance
“…Also other authors [19][20][21] concluded that high ambient temperatures (heat stress) may adversely affect fertilization and embryo survival. Exposure to high temperatures may degenerate ovarian theca and granulosa cells, reduce steroidogenesis, and also compromise ovarian progesterone production [19].…”
Section: Discussionmentioning
confidence: 99%
“…Also other authors [19][20][21] concluded that high ambient temperatures (heat stress) may adversely affect fertilization and embryo survival. Exposure to high temperatures may degenerate ovarian theca and granulosa cells, reduce steroidogenesis, and also compromise ovarian progesterone production [19].…”
Section: Discussionmentioning
confidence: 99%
“…Energy balance was positively correlated with the number of large follicles in ovary, and negatively correlated with the numbers of small and medium follicles [54]. However, cows with medium-sized follicles (between 14.5 and 17.5 mm) had a greater pregnancy rate than cows with follicles of other sizes [55].…”
Section: Discussionmentioning
confidence: 91%
“…A relationship between size of preovulatory follicle and probability of a cow diagnosed as pregnant after a fixed-time AI has been reported in dairy cattle (19) . Cows with preovulatory follicles between 13.5 to 17.5 mm are more likely to become pregnant after a fixed-time AI (20) . A possible explanation for the effect of preovulatory follicle size on pregnancy rate could rely on the degree of oocyte competence.…”
Section: Discussionmentioning
confidence: 99%
“…The cows injected with vitamins C and E had preovulatory follicles falling under the threshold at which the probability of pregnancy after AI increases (20) . Since cows injected with the highest dose of vitamins tend to have a small preovulatory follicles, a similar tendency was expected in estradiol concentrations.…”
Section: Discussionmentioning
confidence: 99%